Economically Feasible Wood Biopreservation Platform in Lannea coromandelica (Houtt.) Merr. Against Wood Rotting Fungus Through Bio-Prospecting Weed Extracts - Gupta, Heena; Sharma, Kulwant Rai; Sharma, J. N. (Frontiers in Plant Science, 2021)
As an alternative to synthetic preservatives, the use of plant-based, environmentally sustainable preservatives for wood protection has tremendous potential. The current research analyzed the dimensional stability and longevity of Lannea coromandelica wood using weed extracts viz. Lantana camara L. and Ageratum conyzoides L., respectively. Petroleum ether and methanolic weed extracts were used to treat wood blocks (5-cm x 2.5-cm x 2.5-cm) at varying concentrations ranging from 0.25 to 2.00%. The petroleum ether extract of A. conyzoides resulted in maximum swelling (tangential plane, 6.30%) at 2.00%, volumetric swelling coefficient (13.17%) at 1.50%, and volumetric shrinkage coefficient (7.71%) at 1.00% concentration, while maximum shrinkage (tangential plane, 4.10%) in methanol extract was observed. In L. camara methanolic extract (1.00%), maximum anti-shrink efficiency (37.01%) was recorded. In vitro mycelial growth of the wood-rotting fungus was completely inhibited by petroleum ether extract from both weeds. However, the methanolic extract of A. conyzoides resulted in maximal inhibition (75.93%) at a concentration of 2.00%. Also; petroleum ether extract (2.00%) of A. conyzoides reduced the fungal colonization to 50%, as compared to control. The lowest weight loss (decay test, 12 weeks) was observed at 2.00% concentration of L. camara petroleum ether extract. The present research highlighted that, both A. conyzoides and L. camara could also be used as an environmentally sustainable wood preservative substitute that will encourage the utilization of Lannea coromandelica in wood-based industries.